Associations Between COVID-19 Symptoms and Psychological Distress - Kim, Ju-Wan; Kang, Hee-Ju; Jhon, Min; Ryu, Seunghyong; Lee, Ju-Yeon; Kang, Seung-Ji; Jung, Sook-In; Shin, Il-Seon; Kim, Sung-Wan; Stewart, Robert; Kim, Jae-Min (Frontiers in Psychiatry, 2021)
Background Hospital isolation for COVID-19 may cause significant psychological stress. The association between COVID-19 symptoms and psychological symptoms has not been systematically studied. We investigated the effects of telephonic intervention on the relationship between psychological symptoms and COVID-19 symptoms at the time of hospitalization and 1 week later. Method We screened 461 patients with COVID-19 for psychiatric symptoms from February 29, 2020, to January 3, 2021. In total, 461 patients were evaluated 2 days after admission, and 322 (69.8%) were followed 1 week later. To assess anxiety and depressive symptoms, the Hospital Anxiety and Depression Scale (HADS) was administered to patients once per week. The Insomnia Severity Index (ISI) and item 9 of the Beck Depression Inventory (BDI-9) were used weekly to assess insomnia and suicidal ideation. Results Of 461 enrolled patients, we observed clinically meaningful psychological anxiety symptoms (in 75/16.3% of patients), depression (122/26.5%), insomnia (154/33.4%), and suicidal ideation (54/11.7%). Commonly reported COVID-19 symptoms are cough/sputum/sneezing (244, 52.9%), headache/dizziness (98, 21.3%), myalgia (113, 24.5%), and sore throat (89, 19.3%). Compared to baseline, significant improvements were found in anxiety, depression, and suicidal ideation at 1 week. No significant group differences in ISI score were observed. Conclusions COVID-19 symptoms at baseline had a significant and persistent negative impact on anxiety and depression at admission and at 1 week after hospitalization. Early intervention is essential to improve the outcomes of patients with mental illness.